Three new paramunnids (Isopoda: Asellota: Paramunnidae) from the Argentine Sea, South-west Atlantic - Doti, Brenda Lía (2016)
Three new species of paramunnid isopods are described: Pentaceration pleonarietis sp. nov., Neasellus argentinensis sp. nov. and N. bicarinatus sp. nov. The three species were collected off Buenos Aires province, the last one was also collected off Chubut province, Argentine Sea. The species belonging to Pentaceration represents the first record of this genus in the Argentine Sea. The diagnostic characters of the genus Neasellus are revised and besides the inclusion of the two new species herein described, a new combination for the species Pelagogonium oculatum Schultz, 1977 is proposed.